STIL Endows Oncogenic and Stem-Like Attributes to Colorectal Cancer Plausibly by Shh and Wnt Signaling - Pradhan, Tapas; Kumar, Vikas; Surya H, Evangeline; Krishna, R.; John, Samu; Jissa, V. T.; Anjana, S.; Chandramohan, K.; Nair, S. Asha (Frontiers in Oncology, 2021)
The discovery of a potent gene regulating tumorigenesis and drug resistance is of high clinical importance. STIL is an oncogene; however, its molecular associations and role in colorectal oncogenesis are unknown. In this study, we have explored the role of STIL gene in tumorigenesis and studied its molecular targets in colorectal cancer (CRC). STIL silencing reduced proliferation and tumor growth in CRC. Further, STIL was found to regulate stemness markers CD133 and CD44 and drug resistant markers thymidylate synthase, ABCB1, and ABCG2 both in in-vitro and in-vivo CRC models. In addition, high expression of STIL mRNA was found to be associated with reduced disease-free survival in CRC cases. Interestingly, we observed that STIL-mediated regulation of stemness and drug resistant genes is not exclusively governed by Sonic hedgehog (Shh) signaling. Remarkably, we found STIL regulate β-catenin levels through p-AKT, independent of Shh pathway. This partially answers Shh independent regulatory mechanism of cancer stem cell (CSC) markers by STIL. Our study suggests an instrumental role of STIL in molecular manifestation of CRC and progression.